Developing children´s soft skills through a design thinking intervention - Penas, Sofia Teles Nunes Galveias (2023)
Companies and organizations are in constant evolution and adaptation in order to maintain their competitivity. This happens while younger generations enter the labor market. Few researchers conducted studies among managers and recruiters, and the lack of soft skills in young people has gained special attention once it plays a crucial role in the personal and professional development of an individual. By using qualitative – direct observation during the intervention – and quantitative – surveys applied before and after the process – methods, this investigation aims to provide evidence of the effectiveness of a design thinking intervention, in school context, as a promoter of soft skills in children. The participants were in the 5th grade, aged between nine and eleven years old. The present investigation evaluates how teamwork, empathy, communication, systemic thinking, creativity, and problem solving, leadership and critical thinking evolved. The results confirm design thinking intervention as a soft skill promoter in children, contributing to the area of education and development. This suggests that through the integration of design thinking in basic school’s curriculum, the soft skills required for personal and professional lives are developed and may contribute to youngsters’ future achievements.